Editors’ Introduction: Power, Plurality, and Democratic Imagination in Asia - Asep Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2022)
This issue of JASSR (Vol. 4, No. 1, 2022) presents a reflection on how power is organized, normalized, and challenged across different Asian contexts. The issue brings together studies on centrism in social media research, school leadership and identity politics in multicultural Indonesia, adat courts in Indonesia’s judiciary system, Muslim social movements in early twentieth-century Cirebon, and democratic erosion in India. Together, the articles show that institutions and ideas cannot be understood only through formal structures or public rhetoric. They must also be examined through history, culture, exclusion, resistance, and lived experience. The issue highlights the value of Asian social science that is historically attentive, conceptually critical, and ethically responsive to struggles over plurality, justice, and democratic life.